Computing task allocation for power Internet of Things including renewable energy sources - Yang, Xianfei; Yu, Xiang; Li, Xiang (Frontiers in Energy Research, 2024)
Focusing on the problem that the large amount of data leads to the long computation delay of cloud computing in the operation control process of power Internet of things (PIOT) including renewable energy sources, this paper establishes a cloud-edge-end collaborative optimization calculation model for PIOT based on edge computation. Combined with data collected by a variety of smart terminal devices (STD) arranged around the power generation equipment, the edge computation framework of the PIOT is analyzed, and computing task allocations model based on minimizing average system latency is established. The corresponding simulation model is built for simulation verification. In comparison with other baseline schemes, it has been demonstrated that the average system latency of all tasks can be significantly decreased by using the proposed optimization scheme.